Effect of glass powder & polypropylene fibers on compressive and flexural strengths, toughness and ductility of concrete: An environmental approach. (October 2021) - Orouji, Maedeh; Zahrai, Seyed Mehdi; Najaf, Erfan
Abstract: Today a wide variety of tools and instruments are made from glass, and they need recycling after being wasted. However, their recycling process could harm the environment. In order to increase concrete ductility and strength against the flexural and compressive loads, one could implement polypropylene fibers to reduce the problems associated with concrete brittleness. In this study, in addition to adopting the environmental sustainability approach and applying glass powder, polypropylene fibers are used. In order to investigate the effect of using glass powder alongside fibers, different compression and flexural beam specimens are made and tested. The rates of used glass are 20, 25, and 30%, and the rates of used fibers are 0.5, 0.75, 1, 1.5, and 2%. Considering the amount of fiber and used waste glass powder, 24 types of compression specimens with dimensions of 15 × 15 × 15 cm and 12 types of flexural beam specimens with dimensions of 50 × 15 × 15 cm were prepared. Based on the test results, the best rate for glass is 25% which causes an increase in the compressive and flexural strengths of the concrete. Also, simultaneous use of 25% glass and 1.5% fibers results in best flexural and compressive strengths of concrete. Simultaneous use of waste glass powder (25%) and fibers (1.5%) improves the compressive strength, flexural toughness, and ductility in the beams by about 1.6, 4, and 13.2 times, respectively.